POWES is pronounced "feminist": Negotiating academic and activist boundaries in the talk of UK feminist psychologists. (November 2022) - Donnelly, Lois C.; Hubbard, Katherine; Capdevila, Rose
The Psychology of Women and Equalities Section (POWES) of the British Psychological Society (BPS) accounts for much of the feminist action in British psychology and beyond. In this qualitative study, we use discursively informed thematic analysis to examine a set of eleven in-depth interviews to explore the everyday experiences of feminists within academic spaces in and around the discipline of psychology in the United Kingdom. Three research questions addressing the boundary between activism and academia; the provision of support; and differing approaches to knowledge production were investigated. Our findings highlight the role of POWES as a feminist community as well as the conceptual importance of notions of home, work, and fun. Moreover, the paper examines the ways traditional conceptions of scientific rigour continue to haunt feminist spaces, as does the invisibility of emotional labour. Overall, our findings indicate that the place of feminist academic communities remains vital to sustain critical thought and action: having an intellectual "home" is pivotal to the survival of feminist psychology as well as feminists in psychology.